Planes [videorecording (DVD)] : from above the world of cars - Lasseter, John ([Publisher not identified], 2013)
Dusty is a cropdusting plane with dreams of competing as a high-flying air racer. But Dusty's not exactly built for racing, and he happens to be afraid of heights. So he turns to a seasoned naval aviator, who helps Dusty qualify to take on the defending champ of the race circuit. Dusty's courage is put to the ultimate test.